Improved Formulation of Travelling Fires and Application to Concrete and Steel Structures. (August 2015) - Rackauskaite, Egle; Hamel, Catherine; Law, Angus; Rein, Guillermo
Abstract: Current design codes and consequently most of the understanding of behaviour of structures in fire are based on the often unrealistic assumption of uniform fire within the enclosure. This assumption is especially wrong in the case of large open-plan compartments, where non-uniform travelling fires have been observed instead. An innovative concept called the Travelling Fires Methodology (TFM) has been developed to take into account this non-uniform fire behaviour. In this study, TFM has been improved to account for better fire dynamics. Equations are introduced to reduce the range of possible fire sizes taking into account fire spread rates from real fires. The analytical equations used to represent the far-field temperatures are presented in continuous form. The concept of flame flapping is introduced to account for variation of temperatures in the near-field region due to natural fire oscillations. These updated near-field temperatures cover a range of temperatures between 800 and 1200 °C, depending on fire size and compartment characteristics. These incorporated changes are based on a fire model which can be used flexibly and adjusted to fit experimental data when it becomes available in the near future. Improved TFM (iTFM) is applied to generic concrete and steel compartments to study the effect of non-uniform heating associated with the travelling fires by investigating the location of the peak temperature along the fire path. It is found to be mainly dependent on the fire spread rate and the heat release rate. Location of the peak temperature in the compartment mostly occurs towards the end of the fire path. Graphical abstract: